Reevaluation of the digestible lysine requirement for broilers based on genetic potential - Dorigam, Juliano Cesar De Paula [UNESP]; Sakomura, Nilva Kazue [UNESP]; Hauschild, Luciano [UNESP]; da Silva, Edney Pereira [UNESP]; Bendezu, Hilda Cristina Palma [UNESP]; Fernandes, João Batista Kochenborger [UNESP] (FapUNIFESP (SciELO), 2014)
Broiler strains available in the poultry industry present different requirements for dietary lysine due to their different growth potentials as a result of their genetic makeup. This study aimed to determine the model parameters for maximum nitrogen retention (NRmaxT), the nitrogen maintenance requirement (NMR) and the efficiency of lysine utilization (bc-1) to reevaluate the lysine (Lys) requirements of male and female broilers. Nitrogen balance trials were performed during three periods (I: 6-21 days, II: 22-37 days, and III: 38-53 days). Seven treatments were used for males and females; the treatments consisted of seven diets with protein levels ranging from 61 to 364 g kg-1 dry matter, with Lys being limiting in the dietary nitrogen (4.91 g of Lys in 16 g of N). Nitrogen intake (NI), excretion (NEX), deposition (ND, ND=NI-NEX) and retention (NR, NR=ND+NMR) values were obtained. The NMR was represented by the exponential relationship between NEX and NI. The NRmaxT and bc-1 were estimated by the exponential fit between ND and NI. The NRmaxT, bc-1, and NMR values were combined in a model to estimate Lys intake by simulating different percentages of the NRmaxT. The Lys intake estimates were 581, 1,538, and 2,171 mg day-1 for males and 512, 1,340, and 1674 mg day-1 for females during periods I, II, and III, respectively. Due to the flexibility of the model, it is possible to calculate the Lys intake for percentages of NR in the range of practical performance data.
Keywords: Amino acid; Exponential model; Maintenance; Nitrogen retention; Performance